Home | | Maths 8th Std | Factorisation

# Factorisation

Type 1: Factorisation by taking out the common factor from each term. Type 2 : Factorisation by taking out the common binomial factor from each term Type 3 : Factorisation by grouping Type 4 : Factorisation using identities Type 5 : Factorisation of the expression (ax2 + bx + c)

Factorisation

Expressing any number as the product of two or more numbers is called as factorisation. The number 12 can be expressed as the product of prime factors like 12 = 2 × 2 × 3. This is called prime factorisation. How will you factorise an algebraic expression? Yes. Expressing an algebraic expression as the product of two or more expressions is called the Factorisation.

Note

A number which is divisible by 1 and itself (or) A number which has only 2 factors are called prime numbers. Example: 2, 3, 5, 7, 11, ...

A number which has more than 2 factors are called composite numbers.Example: 4, 6, 8, 9, 10, 12, ...

For example, (i) a 2 b2 = (a + b)(a b) Here, (a + b) and (a b) are the two factors of a 2 b2

(ii) 5y + 30 = 5( y + 6) , Here 5 and ( y + 6) are the factors of 5y + 30

Any expression can be Factorised as (1) × (expression)

For example, a2 b2 can also be factorised as

(1) × ( a 2 b2 ) or ( 1) × (b2 a2 )

because ‘1’ is a factor for all numbers and expressions

So, when we factorise the expressions, follow the suitable type of factorisation given below to get two or more factors other than 1. Stop doing the factorisation process once you have taken out all the common factors from the expression and then list out the factors.

Type 1: Factorisation by taking out the common factor from each term.

Type 2 : Factorisation by taking out the common binomial factor from each term

Type 3 : Factorisation by grouping

Type 4 : Factorisation using identities

Type 5 : Factorisation of the expression (ax2 + bx + c)

Type 1: Factorisation by taking out the common factor from each term.

Example 3.18

Factorise: 4x 2 y + 8xy

Solution:

We have, 4x 2 y + 8xy This can be written as,

= (2 × 2 × x × x × y ) + (2 × 2 × 2 × x × y)

Taking out the common factor 2, 2, x , y , we get

= 2 × 2 × x × y(x + 2)

= 4xy(x + 2)

Type 2 : Factorisation by taking out the common binomial factor from each term

Example 3.19

(i) Factorise: (2x + 5)(x y ) + (4 y)(x y)

Solution:

We have (2x + 5)(x y ) + (4 y)(x y)

Taking out the common binomial factor (x y)

We get, (x y)( 2x + 5 + 4 y)

(ii) Factorise 3n( p 2) + 4(2 p)

Solution:

We have 3n( p 2) + 4(2 p) (taking – as common) 3n( p 2) 4( p 2)

Taking out the common binomial factor ( p 2)

We get, ( p 2)(3n 4)

Type 3 : Factorisation by grouping

Sometimes, the terms of a given expression are grouped suitably in such a way that they have a common factor so that the factorisation is easy to take out common factor from those terms.

Example 3.20

Factorise : x2 + yz + xy + xz

Solution:

We have, x2 + yz + xy + xz

Group the terms suitably as,

= ( x 2 + xy ) + ( yz + xz)

= x (x + y ) + z( y + x)

= x (x + y ) + z(x + y) (addition is commutative)

= (x + y)[ x + z] [taking out the common factor (x + y) ]

Type 4 : Factorisation using identities

(i) (a + b)2 = a 2 + 2ab + b2

(ii) (a b)2 = a 2 2ab + b2

(iii) a 2 b2 = (a + b)(a b)

Example 3.21

Factorise : x 2 + 8x +16

Solution:

Now, x 2 + 8x +16 can be written as x 2 + 8x + 42

Comparing this with a 2 + 2ab + b2 = (a + b)2 we get a = x ; b = 4

(x2) + 2(x)(4) + (4)2 = ( x + 4)2

x 2 + 8x + 16 = ( x + 4)2

(x+4), (x+4) are the two factors.

Example 3.22

Factorise 49x 2 84xy + 36 y2

Solution:

Now, 49x 2 84xy + 36 y2

72 x2 84xy + 62 y2 = (7x)2 84xy + (6 y)2

Comparing this with a2 2ab + b2 = (ab)2 we get a = 7x , b = 6 y

(7x)2 2(7x)(6 y) + (6 y)2 = (7x6 y)2

49x2 84xy + 36 y2= (7x6 y)2

(7x–6y), (7x–6y) are the two factors.

Try these

Find the factors Example 3.23

Factorise : 49x2 64 y2

Solution:

Now, 49x2 64 y2

72 x2 82 y2 = (7x)2 (8y)2

Comparing this with a2 b2 = (a + b)(a b) we get a = 7x , b = 8y

(7x)2 (8 y)2 = (7x + 8 y)(7x 8 y)

(7x+8y), (7x–8y) are the two factors.

Type 5 : Factorisation of the expression (ax2 + bx + c)

Example 3.24

Factorise x2+ 8x+15

Solution: Given x2 + 8x +15

This is in the form of ax2 + bx + c

We get a = 1,b = 8, c = 15

Now, the product = a × c and sum = b b = 8

=1×15

= 15

= x2 + 8x +15

= x2 + 3x + 5x + 15 (the middle term 8x can be written as 3x+5x)

= (x2 + 3x) + (5x +15)

= x(x + 3) + 5(x + 3) taking out the common factor x+3 )

x2 + 8x + 15 = ( x + 3)(x + 5)

Therefore, (x+3), (x+5) are the two factors.

Think

x2–4(x–2) = (x2–4)(x–2)

Is this correct? If not correct it.

Solution:

Not correct

(3a)2 = 32a2 − 9a2

x2 − 4(x − 2) = x2 – 4x + 8

Example 3.25

Factorise 7c2 + 2c 5

Solution:

Given This is in the form of ax2 + bx + c We get a = 7, b = 2, c = −5

Now, the product = a × c = 7 × (5) = –35 and sum b = 2

= 7c 2 + 2c 5

= 7c 2 5c + 7c 5 (the middle term 2c can be written as –5c+7c)

= (7c 25c) + (7c5)

= c (7c5) + 1(7c5) (taking out the common factor 7c–5 )

= (7c 5)(c + 1)

Therefore, (7c–5), (c+1) are the two factors.

Try these

Factorise the following :

1) 3y +

2) 10x 2 +15y

3) 7m(m 5) + 1(5 m

4) 64 x2

5) x2–3x+2

6) y2–4y–32

7) p2+2p–15

8) m2+14m+48

9) x2x–90

10) 9x2–6x–8

Solution:

1. 3y + 6

3y + 6 = 3 × y + 2 × 3

Taking out the common factor 3 from each term we get 3 (y + 2)

3y + 6 = 3(y + 2)

2. 10x2 + 15y2

10x2 + 15y2 = (2 × 5 × x × x) + (3 × 5 × y × y)

Taking out the common factor 5 we have

10x2 + 15y= 5(2x2 + 3y2)

3. 7m (m − 5) + (15 – m)

7m (m − 5) + (15 – m) = 7 m (m − 5) + (−1 )(−5 + m)

= 7m (m − 5) − 1(m − 5)

Taking out the common binomial factor (m − 5) = (m − 5) (7 m − 1)

4. 64 − x2

64 − x2 = 82x2

This is of the form a2b2

Comparing with a2b2 we have a = 8, b = x

a2b2 = (a + b) (a − b)

64 − x2 = (8 + x) (8 − x)

5. x2 – 3x + 2 x2 – 3x + 2 = x2 − 2xx + 2

= x (x − 2) − (x − 2)

= (x − 2) (x − l)

6. y2 – 4y – 32 y2 – 4y – 32 = y2 – 8y + 4y − 32

= y(y − 8) + 4(y − 8)

= (y − 8) (y + 4)

7. p2 + 2p – 15 p2 + 2p – 15 =  p2 + 5p −3p − 15

= p(p + 5) −3 (p + 5)

= (p + 5) (p − 3)

8. m2 + 14 m + 48 m2 + 14 m + 48 = m2 + 8 m + 6 m + 48

= m (m + 8) + 6 (m + 8)

= (m + 6) (m + 8)

9. x2x – 90 x2x – 90 = x2 − 10x + 9x − 90

= x (x − 10) + 9 (x − 10)

= (x + 9) (x − 10)

10. 9x2 − 6x – 8 9x2 − 6x – 8 = 9x2 − 12x + 6x − 8

= 3x (3x − 4) + 2(3x − 4)

= (3x + 2) (3x − 4)

Tags : Algebra | Chapter 3 | 8th Maths , 8th Maths : Chapter 3 : Algebra
Study Material, Lecturing Notes, Assignment, Reference, Wiki description explanation, brief detail
8th Maths : Chapter 3 : Algebra : Factorisation | Algebra | Chapter 3 | 8th Maths